2018
DOI: 10.1111/xen.12408
|View full text |Cite
|
Sign up to set email alerts
|

Porcine IL‐6, IL‐1β, and TNF‐α regulate the expression of pro‐inflammatory‐related genes and tissue factor in human umbilical vein endothelial cells

Abstract: Whether porcine cytokines are induced after pig-to-primate xenotransplantation and activate human cells remains unknown. First, we investigated the regulation of porcine IL-6, IFN-γ, IL-1β, and TNF-α in xenotransplantation using an in vitro model in which porcine aortic endothelial cells (PAECs) and porcine peripheral blood mononuclear cells (PBMCs) were stimulated with human serum. Downstream cytokines/chemokines were monitored. Pro-inflammatory cytokines (IL-6, IFN-γ, and IL-1β) and chemokines (IL-8, MCP-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Both of the two groups were treated with tocilizumab, and these data suggested that the combination of (a) a graft from several genes genetically modified pig, (b) an effective immunosuppressive regimen, and (c) anti‐inflammatory therapy (eg, tocilizumab and etanercept) would prevent coagulation dysfunction effectively. Moreover, IL‐6 induced the expression of TF in both PAECs and HUVECs . Collectively, although we can reasonably predict that blockade of IL‐6 signaling might be beneficial for inhibiting coagulation dysfunction in xenotransplantation, we cannot reach definite conclusions of IL‐6 in xenotransplantation according to these emerging data.…”
Section: Potential Pathological Role Of Il‐6 In Xenotransplantationmentioning
confidence: 83%
See 2 more Smart Citations
“…Both of the two groups were treated with tocilizumab, and these data suggested that the combination of (a) a graft from several genes genetically modified pig, (b) an effective immunosuppressive regimen, and (c) anti‐inflammatory therapy (eg, tocilizumab and etanercept) would prevent coagulation dysfunction effectively. Moreover, IL‐6 induced the expression of TF in both PAECs and HUVECs . Collectively, although we can reasonably predict that blockade of IL‐6 signaling might be beneficial for inhibiting coagulation dysfunction in xenotransplantation, we cannot reach definite conclusions of IL‐6 in xenotransplantation according to these emerging data.…”
Section: Potential Pathological Role Of Il‐6 In Xenotransplantationmentioning
confidence: 83%
“…In 2017, Iwase and his colleagues demonstrated that the baboon received kidney graft from GTKO/CD46/CD55/EPCR/TFPI/CD47 survived about 8 months while the baboon received graft from GTKO/CD46/TBM died of consumptive coagulopathy at 12 days under the same treatment of immunosuppressive regimens including tocilizumab and etanercept, which suggested that CD55 and anti‐inflammatory therapy (eg, tocilizumab and etanercept) were important for coagulation dysregulation (Table ) . Moreover, TNF‐α increased TF expression in both PAECs and HUVECs . Collectively, blockade of TNF‐α might suppress coagulation dysfunction in xenotransplantation.…”
Section: Potential Pathological Role Of Tnf‐α In Xenotransplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human serum activated NF‐κB signaling in PAECs . We wondered if activation of NF‐κB signaling was responsible for the induction of COX‐2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Human serum activated NF-κB signaling in PAECs. [49][50][51] We won- Figure 3C) and by about 50% at protein level ( Figure 3D). Along with decreased COX-2 expression, p52 processing and phosphorylation of p65 were consistently attenuated by NF-κB inhibitors ( Figure 3D).…”
Section: Complement and Inflammatory Cytokines Induce Cox-2 Expressmentioning
confidence: 99%